Finite‐Element analysis of a rolling contact model with anisotropic elastic material properties. Issue 4 (23rd April 2013) - Karin, I.; Niehuesbernd, J.; Bruder, E.; Lipp, K.; Hanselka, H.; Müller, C.
Abstract The elastic properties of a material are an important factor for the designing and dimensioning of structural and functional components with respect to the dimensional stability, the spring‐back behavior or the fatigue properties. The present work is focused on the impact of the elastic anisotropy on a rolling contact loading of a severely deformed ferritic steel. Linear profiles produced by the newly developed forming process called linear flow splitting are considered to be well suitable as linear guides, due to their reduced surface roughness and highly increased surface hardness. Orientation data obtained by EBSD measurements are used for the calculation of the elastic tensors of the severely deformed parts applying the geometric mean in addition to the classical Voigt and Reuss approaches. The produced profiles exhibit a strong elastic anisotropy in the plane parallel to the desired rolling contact surface showing a strong gradient in forming rate. The evaluation of the stresses in the rolling contact area of the formed microstructure is estimated by the implementation of the determined compliance tensors into a finite element rolling‐contact model. In comparison to results with a homogeneous and isotropic material model the results are analyzed with respect to the rolling contact loading based on the von Mises failure criterion.